SISTEM PEMUNGUTAN PAJAK KENDARAAN BERMOTOR MELALUI LAYANAN SAMSAT KELILING TERHADAP KEPATUHAN WAJIB PAJAK - Setyani Sri Haryanti; Kurniawan Aji Wijaya (STIE AUB Surakarta, 2019)
This study aims to analyze the effect of Tax Access, Facilities, Complain Centers and Websites on Taxpayer Compliance in Boyolali Regency. The population in this study are all Motor Vehicle Taxpayers registered in Boyolali Regency. The sampling technique uses a random sampling technique with a sample size of 100 respondents. The analysis technique consisted of validity test, reliability test, multicollinearity test, autocorrelation test, heteroscedasticity test, normality test, multiple linear analysis, t test, F test, and coefficient of determination. Hypothesis Test Results prove that Access to Tax, Facilities, Complaint Center, and Website have a positive and significant effect on Taxpayer Compliance. F test results prove that Access to Tax, Facilities, Complaint Center and Website together have a significant effect on Taxpayer Compliance. The results of the determination test (R2) prove that overall the effect exerted by the independent variable on the dependent variable was 31.3% while the remaining 68.7% was influenced by other variables or models not included in this study.